HUBUNGAN ANTARA HARGA DIRI DENGAN INTENSI AGRESI PADA ANGGOTA SAT DALMAS DI POLRES SEMARANG - Noveri Puspitasari; Endang Sri Indrawati (Jurnal EMPATI, 2014)
Under Act No 2 of 2002, the controlling force of mass (Dalmas) of Police forces are derived from elements of Brimob and Samapta which prepared and trained specifically to handle the mass disorder and crime. The movements of these force on the fields, were always in the form of groups of platoons (ton), company (ki), battalions (yon) until the detachment (regiment) depending on the type of mass, the mass number and the factual escalation of threats faced in the field. In the process of securing the ground, police members are always faced with a tough negotiation process and mass violent acts rising to the intention of police members to commit acts of violence or aggression. The study was conducted to determine the relationship between self-esteem with the intention of aggression on Sat dalmas members in Semarang Police Resort. The populations of this study were 50 members of Sat dalmas. The number of subjects was determined using the technique of the population study. Collecting data using the self-esteem scale consists of 40 items (α = 0.968) and aggression intention scale consists of 64 items (α = 0.972). Simple regression analysis showed rxy = -0.424 with p = 0.002 (p